2021
DOI: 10.3390/ijms221910628
|View full text |Cite
|
Sign up to set email alerts
|

New Active Packaging Based on Biopolymeric Mixture Added with Bacteriocin as Active Compound

Abstract: The objective of this work was to develop a chitosan/agar-agar bioplastic film incorporated with bacteriocin that presents active potential when used as food packaging. The formulation of the film solution was determined from an experimental design, through the optimization using the desirability function. After establishing the concentrations of the biopolymers and the plasticizer, the purified bacteriocin extract of Lactobacillus sakei was added, which acts as an antibacterial agent. The films were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…The Agar-agar films allow easy interaction with mainly aqueous bioactive extracts. In film synthesis, when the solvent is replaced by an aqueous extract, it allows a homogeneous interaction with the agar-agar matrix [63]. Due to the high compaction of pure agar film, it becomes very brittle.…”
Section: Agar and Chitosan Blendsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Agar-agar films allow easy interaction with mainly aqueous bioactive extracts. In film synthesis, when the solvent is replaced by an aqueous extract, it allows a homogeneous interaction with the agar-agar matrix [63]. Due to the high compaction of pure agar film, it becomes very brittle.…”
Section: Agar and Chitosan Blendsmentioning
confidence: 99%
“…The electrostatic interaction is caused by the -NH 3+ groups of chitosan and -COO − of the ester group of agar-agar [64] in addition to intermolecular interactions through hydrogen bonds between functional groups, such as -OH [65] (Figure 2). The bond between the polymers allows synthesis of a homogeneous film that combines the benefits of both, depending on the concentrations used and the presence or absence of extracts, resulting in materials with particular properties [63]. Cao et al [66] used different concentrations of agar-agar and chitosan, and found th when the proportions of the polymers were equal the permeability to water vapor w reduced.…”
Section: Agar and Chitosan Blendsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of these materials in the production of antimicrobial food packaging containing clay and silicate-, biopolymer-, metal-, nanocellulose-, and layered double hydroxide-based bio-nanocomposites was also described. An additional research article by Contessa et al [ 21 ], entitled “New Active Packaging Based on Biopolymeric Mixture Added with Bacteriocin as Active Compound”, described a chitosan/agar-agar bioplastic film incorporating bacteriocin extracted from Lactobacillus sakei as an antibacterial agent. When used for Minas Frescal cream cheese packaging, this material was shown to contribute to a significant increase in cheese microbiological stability, releasing the active compound into the food during its storage.…”
mentioning
confidence: 99%